The vulnerable community: Women’s shelters during the Covid-19-pandemic (Sociologisk Forskning, 2021)
When the Covid-19 pandemic reached Sweden, women’s shelters mobilized quickly because they knew what a lockdown of public life could mean for women and children who are living with threats and violence in their homes. In a short time, recommendations by the authorities to work at home, maintain social distancing, and avoid travelling resulted in decreased possibilities for mobility. This made it particularly difficult for abused and controlled women to make contacts with the authorities and women’s shelters. The purpose of this article is to understand how the relationship between abused women and the community can be understood in times of pandemic. This is done by applying a theoretical model of “the immunitary life”, to understand the relation between the individual and the community. The study consists of telephone interviews conducted in the spring of 2020 with staff at five different women’s shelters. A central result in the study is that abused women, during the pandemic, are at risk of being deprived of opportunities to create the relationships with the community that women’s shelters otherwise enables.
Keywords: risk; violence; biopolitics; immunitary life; vulnerability; Covid-19; Corona crisis